Da’wahtainment: The Creativity of Muslim Creators in Da'wah Communication on Social Media - Tika Mutia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This article aims to analyze how Muslim creators carry out the creativity of da'wah communication on social media. Da'wah through social media is considered more appealing for the younger generation. This research uses the netnographic method that focuses on observations on research subjects on the internet. The research object is contained in videos on the Instagram social media page @nunuzoo and the Youtube channel of Komedi Dakwah Film. The study results show that the creativity of Muslim creators can be seen from the uploaded content that is presented containing entertaining elements, humorous stories, and da'wah themes that are chosen to follow the trend in demand. The da'wahtainment uploads most sought after by netizens are presented in videos/short films rather than just posting photos and infographics. In addition, da'wah communication carried out by communicators, namely Muslim creators, uses sources that do not conflict with Islamic teachings popular media, and can change the younger generation’s lifestyle to be more Islamic.